1992
DOI: 10.1002/jemt.1070210206
|View full text |Cite
|
Sign up to set email alerts
|

Morphofunctional aspects of the mammalian pineal gland

Abstract: The primary aim of this review is to present the current state of knowledge of the ultrastructure of the mammalian pineal gland, with emphasis on its functional aspects. Basic ultrastructural features of the mammalian pinealocytes are presented with special attention paid to ultrastructural aspects of pineal secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 96 publications
(114 reference statements)
1
12
0
Order By: Relevance
“…At least two kinds of secretory vesicle-like organelles have been identified in pinealocytes: dense core granules, which are speculated to be involved in the storage and secretion of melatonin and some neuropeptides such as arginine vasotocin (3,4), and a large number of synaptic-like microvesicles (MVs) 1 containing synaptophysin (5). Although histochemical evidence indicated that MVs are distinct from neuronal synaptic vesicles in their lack of synapsin I, the possible participation of MVs in some secretory pathways in pinealocytes was also speculated (5).…”
mentioning
confidence: 99%
“…At least two kinds of secretory vesicle-like organelles have been identified in pinealocytes: dense core granules, which are speculated to be involved in the storage and secretion of melatonin and some neuropeptides such as arginine vasotocin (3,4), and a large number of synaptic-like microvesicles (MVs) 1 containing synaptophysin (5). Although histochemical evidence indicated that MVs are distinct from neuronal synaptic vesicles in their lack of synapsin I, the possible participation of MVs in some secretory pathways in pinealocytes was also speculated (5).…”
mentioning
confidence: 99%
“…Its long-term functional "inoperativeness" leads to the release of some ribosomes, complexation of GER cisternae, and secretion of vesicles with a fl occulent agent. These changes illustrate ependymal secretion and suppression of the neurosecretion-like mechanism [8].…”
Section: Resultsmentioning
confidence: 99%
“…Here we studied changes in rat pineal gland after 45 and 90 days of 24-h exposure to bright light. The standard morphological markers served as the index of functional activity of the pineal gland [8].…”
mentioning
confidence: 99%
“…Taking into account the observed increase in the number of vesi cles with osmiophilic inclusions occurring at the new moon (and at the background of hyperplasia of dic tyosomes and an expanding area of the Golgi complex), one can speculate that the vesicles carrying dense inclu sions are formed owing to the Golgi complex of pinealo cytes. It is generally accepted that the functional state of the pineal endocrine cells -light pinealocytes (LP) and dark pinealocytes (DP) -is different [1,2,16]. The observed lunar phase dependent morphological changes can be a reflection of the shifts in the functional state of the pineal gland.…”
Section: Discussionmentioning
confidence: 99%